Visible‐Light Augmented Lithium Storage Capacity in a Ruthenium(II) Photosensitizer Conjugated with a Dione‐Catechol Redox Couple. Issue 42 (13th June 2022) - Gupta, Deepak; Lakraychi, Alae E.; Boruah, Buddha D.; De Kreijger, Simon; Troian‐Gautier, Ludovic; Elias, Benjamin; De Volder, Michael; Vlad, Alexandru
Abstract: Controlling redox activity of judiciously appended redox units on a photo‐sensitive molecular core is an effective strategy for visible light energy harvesting and storage. The first example of a photosensitizer ‐ electron donor coordination compound in which the photoinduced electron transfer step is used for light to electrical energy conversion and storage is reported. A photo‐responsive Ru‐diimine module conjugated with redox‐active catechol groups in [Ru(II)(phenanthroline‐5, 6‐diolate)3 ] 4− photosensitizer can mediate photoinduced catechol to dione oxidation in the presence of a sacrificial electron acceptor or at the surface of an electrode. Under potentiostatic condition, visible light triggered current density enhancement confirmed the light harvesting ability of this photosensitizer. Upon implementation in galvanostatic charge‐discharge of a Li battery configuration, the storage capacity was found to be increased by 100 %, under 470 nm illumination with output power of 4.0 mW/cm −2 . This proof‐of‐concept molecular system marks an important milestone towards a new generation of molecular photo‐rechargeable materials. Abstract : New strategies to address climate change are more urgent than ever. A molecular metallo‐organic bifunctional material with covalently attached photo‐active and redox units led to synchronous light harvesting and energy storage functions. As cathode material in a two‐electrode Li photo‐battery configuration, the storage capacity increased by 100 %, under 470 nm illumination with output power of 4.0 mW/cm −2 .